The Spatial Variance of Divorce Phenomenon in Iraq During the Period 2007-2018 - M. Saleh, Enas; Alhian, Bilal B. (International Journal of Psychosocial Rehabilitation, 2020)
The phenomenon of divorce is one of the most important population phenomena although marriage and intermarriage, the phenomenon of the majority of the living creatures to ensure sustainability but divorce acquired by human beings, it is the opposite of marriage. The subject of divorce received the attention of the competence of several of its perspective as science, psychology and law, and since the divorce population phenomenon spatially institutionalism rationed temporal dimension has been examined from a geographical perspective. It is the study of the phenomenon of divorce in Iraq exceptional significance in a country adopting the policy of encouraging the population to childbearing and fertility rates for long decades of time how will face population phenomenon whose effects are reflected negatively on its objective, in turn, reduce fertility rates, so when they declared the Iraqi outline will depend inevitably on studies dealing with this phenomenon, including Geographical Studies.